PENDAMPINGAN BAGI KELOMPOK ANAK SEKOLAH TENTANG BETERNAK AYAM KAMPUNG SUPER, ARAB SEBAGAI SUMBER PROTEIN HEWANI DI DUSUN AIRLOUW KOTA AMBON - Papilaya, Bercomien Juliet; Ralahalu, Tabitha Naomi; Labetubun, Jusak; Liur, Isye Jean (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Improving the knowledge and skills of school children, especially about raising chickens as a source of animal protein, begins with providing motivation, hard work/business and important basics to them. Raising native chickens has the potential to meet family needs, especially nutrition for children. Animal protein is an essential nutrient that plays an important role in improving children's nutritional status and is a strategic investment for future nutritional health. Protein and fat in meat and eggs can provide the energy needed by children for daily activities. Intensification of native chickens is a government program that has been running since 2000 to increase the population of chickens in order to meet the needs of the community. The general objective is to increase the production of native chickens by identifying superior seeds as males and females. The specific objective is to increase knowledge about the importance of protein, livestock skills, superior native chickens (KUB, Super and Arab). The implementation of community service activities is focused on student groups (teenagers and youth). The results obtained have a positive impact, children's knowledge and skills increase, this can be seen from cooperation in livestock farming. The positive impact of this activity is better chicken livestock production for family needs for meat and eggs, also reducing damage to yard plants and utilization of agricultural waste. The indicator of the success of this activity is around 80% of children who show better attention/response.